Геоэлектрическая модель консолидированной земной коры и верхней мантии вдоль геотраверса Евробридж-97 - Астапенко, В.Н.; Логвинов, И.М. (Геофизический журнал, 2014)
Уздовж профілю Євробридж-97 виявлено 11 локальних об’єктів зниженого опору (ОЗО) за результатами двовимірної інверсії магнітотелуричних зондувань. Більшість об’єктів розташовані в перехідному шарі земної кори. У верхній мантії північної частини Прип’ятського прогину і півдня Українського щита виявлено ОЗО, які просторово відповідають підвищеним значенням теплового потоку. Розглянуто зв’язок ОЗО з сейсмічними розрізами уздовж профілю. Along the profile EUROBRIDGE’97 11 local objects of low resistance (OLR) on the results of the two-dimensional inversion of magnetotelluric sounding have been found. Most of the objects are located in the transition layer of the crust. In the upper mantle of the northern part of the Pripyat Trough and of the south of the Ukrainian Shield conductivity objects spatially consistent with the high values of heat flow were found. Connection of OPS with seismic sections along the profile has been considered.